2022
DOI: 10.1002/nop2.1173
|View full text |Cite
|
Sign up to set email alerts
|

A study on accuracy and precision of fluid volume measurements by nurses, patients and healthy persons in a clinical setting

Abstract: Maintaining a proper fluid balance is essential to ensure functioning of metabolic processes in the body and maintaining health (Armstrong & Johnson, 2018;Diacon & Bell, 2014). The average daily fluid intake varies between individuals. A recent review, which included multiple research studies, found that adults should consume more than 1.8 L of water over 24 hr to maintain adequate hydration (Armstrong & Johnson, 2018). Fluid imbalance results in dehydration or overhydration of patients, with potentially sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ingestion of fluid is sometimes simply missed. Moreover, patients visually underestimate, and healthy volunteers commonly overestimate, the amount of fluid that is contained in a glass, while nurses make the best estimates [24]. Lack of knowledge about how to judge the water content of solid food further reduces the value of visual estimates of fluid intake.…”
Section: Dehydrationmentioning
confidence: 99%
“…Ingestion of fluid is sometimes simply missed. Moreover, patients visually underestimate, and healthy volunteers commonly overestimate, the amount of fluid that is contained in a glass, while nurses make the best estimates [24]. Lack of knowledge about how to judge the water content of solid food further reduces the value of visual estimates of fluid intake.…”
Section: Dehydrationmentioning
confidence: 99%
“…Studies have shown that even trained healthcare professionals, such as nurses, have difficulty in accurately estimating fluid volumes. For example, one study found that 50% of nursing staff estimated volumes within an error margin of 10% and all nurses estimated within an error margin of 25% [ 33 ]. Another study found that only 27% of nurse’s estimates were within an error margin of 10% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calculation errors pointed to in this review may be prevented by using electronic patient records, where fluid balance calculations are performed automatically and are no longer based on human calculation 39 44 62. By exclusively using fluid containers with measuring lines or through automated measuring inaccuracies related to estimations can be avoided 22 23. Additionally, interactive teaching based on daily practice for all stakeholders54 69 and involving and motivating patients to self-monitor may enhance quality 46 67.…”
Section: Discussionmentioning
confidence: 99%
“…Further, fluid volumes are estimated based on visual assessment. Studies have shown such estimations are unreliable22 23 and affected by, for example, the colour of the fluids and the shape of the container used 23 24. To clarify the scope and characteristics of the problem, a systematic overview of the literature can provide information on the quality of fluid balance in different wards and settings along with possible interventions to improve fluid balance charting.…”
Section: Introductionmentioning
confidence: 99%